Marketing Strategy Development for Green House Karamba Hydroponic Vegetables - Nurjanah, Audra Siti; Nurhayati, Popong; Ramadanti, Annisa (School of Business, Bogor Agricultural University (SB-IPB), 2022)
Green House Karamba, as a hydroponic vegetable producer, faces fluctuating sales volume and difficulty in reaching the end consumer. Therefore, Green House Karamba needs strategy formulation. This study aimed to: (1) analyze the ekisting marketing strategy of Green House Karamba based on marketing mix 4C; (2) analyze the competitive advantage of Green House Karamba based on competitive conditions; and (3) formulate a marketing strategy that can be applied by the company. This study focused on the products of hydroponic vegetables of Green House Karamba. Marketing mix 4C analysis, Porter’s five forces model, and marketing genius approach were employed for this study. Based on marketing mix 4C analysis, there were rooms for improvement in co-creation, communal activation, and conversation. According to Porter’s five forces model analysis, Green House Karamba’s potential competitive advantage were in terms of price and quality, relative independent production, and differentiation. The results of the previous analyses were considered for strategy formulation using a marketing genius approach. Based on marketing genius analysis, comprehensive marketing strategy and value proposition development were recommended for Green House Karamba. This study is expected to help Green House Karamba in facing competition. Keywords: hydroponic, marketing genius, marketing mix 4C, marketing strategy